The learning curve associated with anteromedial portal drilling in ACL reconstruction. Issue 2 (2nd April 2016) - Luthringer, Tyler A.; Blackmore, Shane A.; Singh, Brian C.; Strauss, Eric J.
ABSTRACT: Objectives : The objective of the current study was to evaluate the accuracy and precision of femoral and tibial tunnel placement during anterior cruciate ligament reconstruction (ACLR) using independent anteromedial portal (AMP) drilling over a three-year observation period. Methods : This study was a retrospective review of 161 consecutive primary ACL reconstructions from a single surgeon over his first 36-months in practice. Femoral and tibial tunnel angulation measurements were made on anteroposterior radiographs by a single observer utilizing the assessment method described by Aglietti et al. The accuracy and precision of tunnel placement across the three-year period were assessed with comparisons made. Results : Significantly improved accuracy was demonstrated toward the cadaveric ideal femoral tunnel angle of 33.5° over time. Improved precision of tunnel placement was also demonstrated evidenced by declining standard deviations across each year. Statistically significant improvement in femoral tunnel placement was seen between the first and second cohorts of 32 cases. No significant change was seen with respect to tibial tunnel angle across the observation period. Conclusions : A learning curve in developing accuracy and precision in ACL femoral tunnel placement using the AMP technique exists; our study indicates this to be somewhere between 32 and 64 cases. Tibial tunnel placement does not share the same learning curve using this surgical technique.